A Study on Behavioral Pediatric Feeding Status: Maternal Opinions : Pediatric Feeding Status: Maternal Opinions - Ozgen, Leyla; Unusan, Nurhan (Progress in Nutrition, 2021)
Summary. Aim: This research aimed to examine behavioral feeding status in children aged 6-8 according to maternal opinions. The research investigated if Behavioral Pediatrics Feeding Assessment Scale (BPFAS) overall score differed significantly by family structure, mother’s history of nutrition education and child’s history of health problems and medication use. Materials and methods: The population was Kocaeli province, while the sample comprised 245 children and their mothers selected with convenience sampling from primary schools in Kocaeli Turkey. Data analysis: The study data were gathered with a questionnaire form and the Behavioral Pediatrics Feeding Assessment Scale. Mann Whitney U tests were conducted to investigate if BPFAS subscale scores differed by mother’s history of nutrition education, and if BPFAS overall score differed by family structure, mother’s history of nutrition education and child’s history of health problems and medication use. Differences in BPFAS overall score by child’s Body Mass Index (BMI), age group and parents’ educational attainment were analyzed with Kruskal Wallis H tests. Results and discussion: 54.3% of the children participating in the study were female, while the percentages of the children aged 6, 7 and 8 were 21.2%, 28.6% and 50.2%, respectively. 64.5% of the children were underweight and 4.1% were overweight according to their BMI. Mean maternal and paternal ages were 35.4 ±1.1 and 39.6±1.1 years, respectively. In the study, a standard deviation greater than two was indicative of pediatric feeding behaviors. The majority of the children’s BMI was below 18.5, suggesting an inadequate and unbalanced nutritional behavior, which can be considered an indicator of incipient malnutrition. Conclusions and suggestions: the researchers recommend popularizing nutrition education in schools as a government policy to combat childhood underweight and malnutrition.